Al-Maʿarrī’s Anxious Menagerie: The Epistle of the Horse and the Mule - Blankinship, Kevin (Journal of Abbasid Studies, 2021)
Abstract Around the year 411/1021, blind author and controversial freethinker Abū l-ʿAlāʾ al-Maʿarrī (449/1057) wrote Risālat al-ṣāhil wa-l-shāḥij (The Epistle of the Horse and the Mule), a meandering prose work populated by animal characters who talk about Syrian society on the eve of the crusades. The story exudes a brand of fictionality, namely creative literary exaggeration designed to call forth mental pictures, that sets it apart from other animal texts due to the overwhelming ambiguity it creates. The animal characters suffer existential anxiety when, for instance, they realize that concepts like genus (jins) and species ( nawʿ ) turn out to be fuzzier than they thought, thereby calling into question whether any species—be it biological or linguistic—is a stable class. Animal ontology gets further confused by just-so stories about hybrids and crossbreeds, and by terms for philosophical contingency that question whether talking animals even exist—this is not just a story that did not happen, but a story that cannot happen except in the imagination. On the other hand, those same philosophical terms may yet affirm that speaking animals could exist, and that they have value in themselves, by hinting at their place in a cosmic order that radiates the goodness of its Source.